Is God partial in creation? A feminist re-examination of gender in the Yahwist’s narrative - Uzoma A. Dike; Paulinus O. Agbo (Verbum et Ecclesia)
Traditional Christian patriarchy and primacy of the male gender, at any rate, are linked to the Yahwist creation narrative in which the man is seemingly created before the woman. Prevailing conversations have constructed doctrinal positions, polity and dogmatism around the tradition of male headship and female subjugation. The objective of this study was to reread the Yahwist narrative with the view of demystifying the male headship mythology through a systematic analysis of the interconnection between adam and Adamah. The study utilised grammatical and syntactical exegesis and feminist hermeneutics to advance informed constructions on demystifying male headship. While the grammatical and syntactical focused on the grammar and word ordering of the text to arrive at the authorial intended meaning, the feminist hermeneutics renders interpretation from the women’s experience. Despite eisegetical tendencies surrounding some interpretations of the text of Genesis 2:21–25, the study adds to the discourses on a systematised derogatory view of the feminine gender by the Yahwist. This account presents gender asymmetry as it relates to biblical studies.